FRA and IRS Pricing and Valuation - Rolák, Martin; Baran, Jaroslav; Kolman, Marek; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2013)
This bachelor thesis describes the evolution of the pricing and valuation framework of forward rate agreements (FRA) and fixed-for-floating interest rate swaps (IRS) induced by the financial crisis of 2007-2008. The first part of the thesis reviews the pre-crisis framework, the pricing and valuation formulas of the selected derivatives are presented. It is shown how one could use a single curve for both estimating the derivative payoff and discounting. The first part concludes with the assumptions underlying the pre-crisis framework. In the second part, the provided market evidence of post-crisis market conditions shows that the assumptions from the first part can no longer be deemed valid. In response to the new market conditions, the post crisis framework is introduced. The focus is on the collateralized FRA and IRS, for which the pricing and valuation formulas are derived. This part also discusses the effects of derivative collateralization and the switch to OIS discounting.
Vedoucí práce: Jaroslav Baran
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: finance [obor bakal. práce]; bakalářské práce; bachelor's theses